2016
DOI: 10.1016/j.apenergy.2016.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analyses of the Danish industry sector

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Overall, the energy analysis and exergy analysis of UWCAES system guide significantly different directions for optimization. Similar conclusions are also found in other studies . This is because the energy analysis is based on the first law of thermodynamics while the exergy analysis is based on the second law.…”
Section: Energy and Exergy Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, the energy analysis and exergy analysis of UWCAES system guide significantly different directions for optimization. Similar conclusions are also found in other studies . This is because the energy analysis is based on the first law of thermodynamics while the exergy analysis is based on the second law.…”
Section: Energy and Exergy Analysessupporting
confidence: 90%
“…The local loss coefficients are calculated by following equations. [34][35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Pressure Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, the changes applied to Table 2 were the following: increasing Mean T p by all sectors; raising the high range Electrical Heating η (%) from 70 to 75 and increasing the three ranges of Fuel Heating efficiencies (%) to 70, 85 and 100 [42]. To compute the energy and exergy efficiencies shown in Table 3, an extensive investigation was developed to find wider criteria and data of industrial end-use heating temperatures from different manufacturing activities [50][51][52][53]. We utilized the data from Table 2 and the quality factors from Table 1.…”
Section: Computation Of the Thermodynamic Efficiencies: Energy (η) Anmentioning
confidence: 99%
“…The authors found an exergy conversion performance of 1.3% for households and 38.5% for the tertiary sector. In the past 20 years, several other exergy-based sectoral studies have been developed for countries such as the U.K. (Brockway et al, 2014;Gasparatos et al, 2009;Hammond and Stapleton, 2001), Italy (Wall et al, 1994), Norway (Ertesvåg, 2001), Turkey (Rosen and Dincer, 1997;Utlu and Hepbasli, 2003), China (Chen and Chen, 2006;Brockway et al, 2015), Mexico (García Kerdan, Morillón Gálvez et al, 2015), Jordan (Al-Ghandoor, 2013), U.S. (Reistad, 1980), Denmark (Bühler et al, 2016), and Canada (Rosen, 1992). Rosen (2013) described that exergetic-based sectoral analysis showed that actual efficiencies in the building sector are lower than the perceived inefficiencies commonly published in government annual reports, while in sectors such as the transportation and utility the efficiencies are higher than the perceived efficiencies.…”
Section: Building Stock Modelsmentioning
confidence: 99%